2022
DOI: 10.1016/j.ultsonch.2022.105924
|View full text |Cite
|
Sign up to set email alerts
|

Removal of field-collected Microcystis aeruginosa in pilot-scale by a jet pump cavitation reactor

Abstract: Highlights Jet pump cavitation reactors inhibited the photosynthetic activity and growth of M. aeruginosa. Jet pump cavitation reactors caused serious rupture to M. aeruginosa cells. Plausible cell disruption mechanisms were proposed with fluorescence microscope and SEM. The algal cell disruption efficiency was improved by optimizing flow conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In recent years, a lot of significant studies has been conducted into the experimental, numerical simulation and application of JPCRs. Xu et al [26] conducted a HC disinfection test with a JPCR for a cell suspension containing Microcystis aeruginosa; the results showed that JPCR could effectively inhibit photosynthetic activity of algal cells, and the cell disruption efficiency of JPCR was improved in the limited cavitation stage. Meng et al [27] investigated the extent of chlortetracycline (CTC) degradation using a combination of the venturi tube hydraulic cavitation device and the oxidizing agent hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of significant studies has been conducted into the experimental, numerical simulation and application of JPCRs. Xu et al [26] conducted a HC disinfection test with a JPCR for a cell suspension containing Microcystis aeruginosa; the results showed that JPCR could effectively inhibit photosynthetic activity of algal cells, and the cell disruption efficiency of JPCR was improved in the limited cavitation stage. Meng et al [27] investigated the extent of chlortetracycline (CTC) degradation using a combination of the venturi tube hydraulic cavitation device and the oxidizing agent hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to better cavitation performance and more efficient energy utilization, the rotational hydrodynamic cavitation reactor (RHCR) has been investigated in various industrial fields [27] , [28] , [29] , [30] , [31] . Pongraktham and Somnuk [32] explored the treatment of sludge palm oil by RHCR with cylinder holes in the rotor to reduce the free fatty acid content.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic cavitation has attracted attention in various contexts including chemical reactors [1] , [2] , water treatment [3] , [4] , [5] , biochemical engineering [6] , synthesis of biodiesel [7] , [8] , [9] , ex-situ biological hydrogen methanation [10] , as well as degradation of harmful substances such as bisphenol [11] , sulfamerazine [12] , ammonia nitrogen [13] , fatty acid [14] , microcystis aeruginosa [15] . Several types of cavitating devices have been proposed, such as Venturi type [16] , jet type [17] , swirling vortex type [18] and rotor type [19] .…”
Section: Introductionmentioning
confidence: 99%